2022
DOI: 10.1186/s12888-022-04403-2
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 related anxiety and its associated factors: a cross-sectional study on older adults in Bangladesh

Abstract: Background The COVID-19 pandemic has resulted in serious mental health conditions, particularly among older adults. This research explored the prevalence of COVID-19-related anxiety and its associated factors among older adults residing in Bangladesh. Methods This cross-sectional study was conducted among 1,045 older Bangladeshi adults aged ≥ 60 years through telephone interviews in September 2021. A semi-structured interview schedule was used to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
1
5
2
Order By: Relevance
“…Due to the lack of studies conducted among adolescents, comparison with similar studies challenged us. However, the magnitude of COVID-19-related anxiety reported in this study is in line with the magnitude reported in United Kingdom (21.3%) among the general population [ 31 ], Bangladesh (23.2%) among older adults [ 32 ], and South and Southwest Ethiopia (20.2%) [ 33 ] among healthcare professionals. But the findings of the research conducted in Philippines (37.8%) [ 34 ], China (70.78%) [ 35 ], and Northern Ethiopia (63%) [ 36 ] appear to be higher than the magnitude reported in our study.…”
Section: Discussionsupporting
confidence: 90%
“…Due to the lack of studies conducted among adolescents, comparison with similar studies challenged us. However, the magnitude of COVID-19-related anxiety reported in this study is in line with the magnitude reported in United Kingdom (21.3%) among the general population [ 31 ], Bangladesh (23.2%) among older adults [ 32 ], and South and Southwest Ethiopia (20.2%) [ 33 ] among healthcare professionals. But the findings of the research conducted in Philippines (37.8%) [ 34 ], China (70.78%) [ 35 ], and Northern Ethiopia (63%) [ 36 ] appear to be higher than the magnitude reported in our study.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, patients with LLD who had to walk more than 30 min to reach a medical centre were more likely to develop COVID-19 anxiety, which contrasts with a study conducted in Bangladesh 26. A plausible explanation may be that individuals living in close proximity to medical centres find it easier to access medical care and have not experienced challenges in seeking medical assistance during the pandemic.…”
Section: Discussioncontrasting
confidence: 75%
“…Sample sizes for each partition were calculated, and participants were selected accordingly. Taking into account a prevalence of 23.2%26 and a margin of error of 5%, a sample size of 1133 was calculated at a 95% CI, 90% test power and 95% response rate. Considering the loss rate of 20%, the required sample was 1417.…”
Section: Methodsmentioning
confidence: 99%
“…Emerging evidence during the COVID-19 pandemic shows that mental health outcomes, including anxiety, stress and depression, affected almost everybody globally (Mistry et al, 2022 ; Robinson et al, 2022 ; Xiong et al, 2020 ). The COVID-19 pandemic exerted a detrimental psychological impact at both individual and community levels (Salari et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%